Allele frequency and genotype distribution of aldo keto reductase 1D1 (AKR1D1) rs1872930 genetic variant in a Macedonian population - Kapedanovska Nestorovska, Aleksandra; Naumovska, Zorica; Jakjovski, Krume; Sterjev, Zoran; Matevska Geskovska, Nadica; Dimovski, Aleksandar; Shuturkova, LJubica (Macedonian Pharmaceutical Association, 2018)
AKR1D1 has been recently recognized as novel candidate gene regulating CYP450 coexpression. The AKR1D1 3’-UTR SNP (rs1872930) functional genetic variation was considered as important source of phenotypic variation in the activity of CYP450. The minor allele frequency of rs1872930 varies among populations suggesting population specific pharmacogenetic implications. The aim of the present study was to determine the AKR1D1 (rs1872930) minor allele frequencies and genotypes distribution in a population from Republic of Macedonia. Four hundred and fifty unrelated Macedonian subjects were studied. AKR1D1 variant allele was detected by real time polymerase chain reaction. The distribution of AKR1D1*1/*1, *1/*36 and *36/*36 genotypes was 0.569, 0.360 and 0.071, respectively. The overall frequency of AKR1D1*36 variant allele was 0.251. Our study is the first to assess the frequency distribution of the AKR1D1*36 (rs1872930) genetic variant in population from Republic of Macedonia and the findings are in accordance with the frequency reported for the Caucasian population. Keywords: AKR1D1, rs1872930, CYP450, variability, gene expression, enzyme activity